Multiplexní dideoxynukleotidové sekvenování s polyadenylovanými sekvenačními primerym - Beránek, Martin; Drastíková, Monika; Petera, Jiří (Chemické listy, 2013)
The title method is applied to one of the analyzed amplicons. The new approach is used for identification of C282Y (C), H63D (H), and S65C (S) mutations in the HFE gene. In a group of DNA samples from 40 patients with suspected hereditary hemochromatosis we amplified specific parts of HFE exon 2 (208 bp) and exon 4 (189 bp) by multiplex PCR. Purified amplicons were subsequently used in a multiplex cycle sequencing reaction containing a hyperadenylated reverse primer for exon 2. Adenylation with a 105-nucleotide polyadenylated tail attached to the 5' end of the primer significantly prolonged the migration time of the exon 2 amplicons in the electrophoretic capillary. This enabled us to obtain separated sequencing data for both the studied amplicons. The numbers of identified zygotes and allelic frequencies in the patients are given. We found six subjects with the risk of hereditary hemochromatosis (15 %). The new method is a faster and cheap alternative to dideoxynucleotide sequencing using standard sequencing primers. Hyperadenylation makes it possible to obtain complete information about the presence or absence of C282Y, H63D and S65C mutations in the HFE gene from one-capillary electrophoretic analysis.
Keywords: DNA Mutational Analysis; polymerázová řetězová reakce; MicroRNAs; Hemochromatosis; Česká republika; mikro RNA; Sequence Analysis, DNA; poly(A)-polymerasa; sekvenční analýza DNA; hemochromatóza; techniky amplifikace nukleových kyselin; 3' nepřekládaná oblast; DNA vazebné proteiny; Electrophoresis, Agar Gel; polyadenylace; genetické nemoci vrozené; 5' Untranslated Regions; Polynucleotide Adenylyltransferase; mutační analýza DNA; 5' nepřekládaná oblast; Nucleic Acid Amplification Techniques; Czech Republic; Polyadenylation; Polyribonucleotide Nucleotidyltransferase; lidé; RNA-Binding Proteins; Humans; DNA-polymerasa I; Genetic Diseases, Inborn; 3' Untranslated Regions; polynukleotidfosforylasa; Polymerase Chain Reaction; elektroforéza v agarovém gelu; DNA-Binding Proteins; DNA Polymerase I; proteiny vázající RNA